The Analysis of the Use of Intercooler on a Multi Stage Cold Storage Simulator Toward the Compressor Work - I Putu Sastra Negara; Ni Ketut Rusminingsih (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
Multistage type cold storage is a refrigeration machine required in an industry because it functions to store food products for a long time. Bali, as a world tourist destination, will rely heavily on this cooling system in preparing services for tourists, especially in the food and beverage sector. Multistage type cold storage is designed to reach the evaporator temperature below -30oC thus the used compressor performance must be able to produce maximum refrigeration effect. Two compressors placed in succession or connected in series complete this cold storage system, which is expected to achieve higher operating pressures. The temperature occurring due to the pressure increase on the second compressor will be anticipated by installing an intercooler aiming at preventing excessive heat or over heat during the compression. The extent to which the important role of the intercooler as a stabilizer of operating temperature in this cooling cycle will be shown in its working cycle with a Mollier diagram (P-h diagram). The data obtained during the operation of the multistage type cold storage is then transferred to the P-h diagram of R134A to determine the cycle diagram and the enthalpy which then determines the amount of COP, the maximum temperature achieved by the system, and its energy requirements. The calculation results obtained using the intercooler COP is 1.83, and the maximum temperature achieved is 67oC, and the energy consumption seen from the total entalphy difference due to compression work is 81 kJ/kg. Without using the intercooler, the system’s COP is 1.72 and the maximum temperature achieved is 94.9oC and 86 kJ/kg of energy consumption. The energy required for the operational becomes more eficient and the heat released to the environment is much less, therefore the multistage cold storage with intercooler can be categorized as an eco-friendly technology.